Answer:
7
Step-by-step explanation:
Answer:
-263
Step-by-step explanation:
replace x by -9
Answer:
-1
Step-by-step explanation:
You can try them out and see which one works.
a: f(2) = f(1) +6 = 5+6 = 11 . . . . . . not this one
b: f(1) = f(2) -6 = -1-6 = -7 . . . . . . not this one (5 ≠ -7)
c: f(2) = f(1) - 6 = 5 - 6 = -1 . . . . . this gives the right f(2)
d: f(2 = -6(f(1) = -6(5) = -30 . . . . not this one
_____
The appropriate choice is ...
... f(n +1) = f(n) - 6
— — — — —
You can also recognize that the next term is 6 less than the current one, so f(n+1) = f(n) - 6, which corresponds to the 3rd selection.
Answer:
8 times 34= 272
Step-by-step explanation: